2015
DOI: 10.1002/oby.21067
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative analysis of hypothalamic damage on MRI predicts risk for hypothalamic obesity

Abstract: ObjectiveExcessive weight gain frequently occurs in patients with hypothalamic tumors and lesions leading to hypothalamic obesity (HO).MethodsDigital brain magnetic resonance imaging (MRI) and clinical outcomes were studied retrospectively in a single center, including 45 children with postoperative lesions in the sellar region (41 craniopharyngiomas, 4 with Rathke's cleft cysts), ∼5 years post‐surgery, mean age 13.9 years. Four standard sections covering hypothalamic areas critical to energy homeostasis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 40 publications
5
104
2
3
Order By: Relevance
“…Thus, it was also observed that diabetes insipidus acted as an endocrine marker of risk for hypothalamic obesity. 12 On the contrary, in our study, no statistically significant differences were observed in the scale of obesity between patients with and without diabetes insipidus. However, the difference in the BMI Z-score was overwhelming: 64% of patients with diabetes insipidus were obese whereas all those without this condition had a normal weight.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Thus, it was also observed that diabetes insipidus acted as an endocrine marker of risk for hypothalamic obesity. 12 On the contrary, in our study, no statistically significant differences were observed in the scale of obesity between patients with and without diabetes insipidus. However, the difference in the BMI Z-score was overwhelming: 64% of patients with diabetes insipidus were obese whereas all those without this condition had a normal weight.…”
Section: Discussioncontrasting
confidence: 84%
“…10 In addition, insulin resistance measured using the homeostasis assessment model (HOMA) before the surgery correlates to post-operative weight gain. 11,12 Although this is a relatively benign disease, the combination of severe hypothalamic obesity and associated comorbidities results in a reduced quality of life. 13 Based on the preceding concepts, we proposed to study the presence of obesity and metabolic complications in a cohort of patients under follow- 17 Baseline energy expenditure was recorded using an indirect calorimetry measuring O 2 consumption and CO 2 production (CCM Express, MEDGRAPHICS) for 20 minutes after 20 minutes at rest.…”
Section: Introductionmentioning
confidence: 99%
“…Así, también, se encontró que la presencia de diabetes insípida fue marcador endócrino de riesgo de obesidad hipotalámica. 12 Contrario a esto, en nuestro trabajo, no se hallaron diferencias estadísticamente significativas en la magnitud de obesidad entre los pacientes con y sin diabetes insípida. Sin embargo, la diferencia de SZ-IMC fue abrumadora, ya que el 64% de los pacientes con diabetes insípida eran obesos, mientras que los que no presentaron dicha patología eran normopeso en su totalidad.…”
Section: Discussionunclassified
“…Esto sustentaría que el compromiso hipotalámico es el 10 Además, la insulinorresistencia medida por el modelo de evaluación homeostática (homeostasis assessment model; HOMA, por sus siglas en inglés) previa a la cirugía se correlaciona con la ganancia de peso posquirúrgica. 11,12 S i b i e n s e t r a t a d e u n a e n f e r m e d a d relativamente benigna, la combinación de obesidad grave de origen hipotalámico y las comorbilidades asociadas a ella disminuyen la calidad de vida. 13 Sobre la base de los conceptos previos, nos propusimos estudiar la presencia de obesidad y complicaciones metabólicas en una cohorte de pacientes seguida en nuestro Hospital, con antecedente de resección de craneofaringioma en la infancia.…”
Section: Introductionunclassified
“…The strongest weight gain occurs during the first 12 months following surgery [14]. In a study conducted in the St. Jude Children's Research Hospital, 65% of 55 patients treated for craniopharyngioma during childhood (about 90% surgery plus radiotherapy) were found overweight or obese after 7.6 years (range 5-21.3 years) from diagnosis [15].…”
Section: Craniopharyngioma and Hypothalamic Obesitymentioning
confidence: 99%